Improving accuracy using low cost GPS and mobile gis devices-prototyping for environmental management tasks - Ivin Amri Musliman, 1979-; Fakulti Kejuruteraan dan Sains Geoinformasi (Skudai : Penerbit Universiti Teknologi Malaysia, 2007)
PSZJBL